Путь к урану (Воспоминания участников поисков и разведки месторождений урана, меди, флюорита) - Зенченко В. П. Владимир Петрович; Гаврилов Л. П. Леонид Павлович (Иркутск, [Б. и.], 2015)
Урановой геологии 70 лет. 1945-2015 гг.